PENGARUH PERSEPSI KETIDAKPASTIAN LINGKUNGAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN DENGAN SISTEM PENGENDALIAN MANAJEMEN SEBAGAI VARIABEL INTERVENING - Angraeni, Rani; Sari, Ria Nelly; Susilatri, Susilatri (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This research was conducted at Bank Perkreditan Rakyat company registered inPerbarindo Riau, Pekanbaru. The purpose of this study is to determine theperception influence of environmental investment, company size on companyperformance with management control system as intervening variable. To achievethe objective, the researcher used the sampling census method, So, therespondents for data collection are all middle level managers and top managers at19 BPR offices in city Pekanbaru. This research is in the form of quantitativeresearch, where the data obtained through questionnaires spread. The analyticaltechnique used is Structural Equation Modeling (SEM) with calculations performedusing WarpPls 5 aids and interveing variables measured by second-order constructanalysis, where the construct latent variable can consist of various dimensions orcomponents so it is called multidimensional construct and each dimensionMeasured by several indicators. The results of the research indicate that: 1) theperception of environmental uncertainty has an influence on the managementcontrol system (belief system, boundary system, diagnostic system and interactivesystem), 2) the size of the company that continues to grow rapidly does not affectthe management control system, 3) management control system (belief system,boundary system , Diagnostic system and inrteractive system) have an influence oncompany performance, 4) the perception of environmental uncertainty has no effecton the company performance through management control system (belief system,boundary system, diagnostic system and inrteractive system); 5) firm size has noeffect on Company performance through management control system (beliefsystem, boundary system, diagnostic system and inrteractive system).